Manajemen karir untuk menyongsong kehidupan di masa depan - Kurniawan, Mochamad Riski Fajar (Maliki Interdisciplinary Journal, 2024)
Career management is becoming increasingly crucial in the era of globalization and rapid technological developments. This article discusses the importance of career management in facing future challenges and opportunities. With dynamic changes in the world of work, individuals are required to be more proactive in planning and managing their careers. Effective career management involves not only short-term planning, but also a clear long-term vision. In this context, career management involves a series of strategic steps ranging from self-assessment, career planning, skills development, to adaptation to changes in the job market. Self-assessment helps individuals understand their personal strengths, weaknesses, interests, and values. Career planning then leads them to set realistic goals and steps to achieve them. Skills development is an important component of career management. The digital era requires workers to continuously update and improve their skills, especially in information and communication technology. Apart from that, soft skills such as communication, collaboration and time management skills are also very necessary. Adaptation to change is another key in career management. With good career management, individuals can be better prepared to face a future full of uncertainty and change.